Neighborhood Liturgy: Mister Rogers and Liturgical Formation - Whitlock, Michelle. L. (Liturgy, 2025)
Mr. Rogers’ Neighborhood was a unique children’s television show that generations of children, and their care givers, looked forward to everyday. The repeated practices of the show shaped the viewers into a community of practice around shared human concerns. Viewers were welcomed into Mr. Rogers’ television home to learn about real life issues. They traveled with Rogers to the imaginary Land of Make Believe. The show created a “sacred space” for people of all ages to learn and grow through play and imagination. Worship also functions as a community of practice. According to Etienne Wenger, communities of practice shape identity through the practices of an ongoing community. They create meaning through shared rituals and narratives. This article applies Etienne Wenger’s understanding of communities of practice to the virtual community created by Fred Rogers and draws on this work to suggest neighborhood practices for intergenerational worship.